The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2174/1566524013666131111121733
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot-Based Nanoprobes for In Vivo Targeted Imaging

Abstract: Fluorescent semiconductor quantum dots (QDs) have attracted tremendous attention over the last decade. The superior optical properties of QDs over conventional organic dyes make them attractive labels for a wide variety of biomedical applications, whereas their potential toxicity and instability in biological environment has puzzled scientific researchers. Much research effort has been devoted to surface modification and functionalization of QDs to make them versatile probes for biomedical applications, and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 166 publications
(180 reference statements)
2
29
0
Order By: Relevance
“…The superior optical and electronic properties of QDs over conventional organic dyes, such as high brightness, high photostability, continuous absorption, narrow emission bandwidth, and the ability to simultaneously excite multiple fluorescent colors, make them attractive labels for the development of QDs-IHC imaging for multiplexing cancer biomarker detection on FFPE tissues. 24,25 In our study, we confirmed that QDs-IHC is a simple and standardized method for detecting EGFR mutations, and it has high sensitivity and specificity when compared with real-time PCR. In addition, the development of specific antibodies against EGFR mutation proteins might be useful for the diagnosis and treatment of lung cancer.…”
Section: Discussionsupporting
confidence: 74%
“…The superior optical and electronic properties of QDs over conventional organic dyes, such as high brightness, high photostability, continuous absorption, narrow emission bandwidth, and the ability to simultaneously excite multiple fluorescent colors, make them attractive labels for the development of QDs-IHC imaging for multiplexing cancer biomarker detection on FFPE tissues. 24,25 In our study, we confirmed that QDs-IHC is a simple and standardized method for detecting EGFR mutations, and it has high sensitivity and specificity when compared with real-time PCR. In addition, the development of specific antibodies against EGFR mutation proteins might be useful for the diagnosis and treatment of lung cancer.…”
Section: Discussionsupporting
confidence: 74%
“…It is a challenge to study the in vivo biodistribution and toxicology of quantum dots in animal systems that could potentially mimic its toxicity in human use. In future, fabrication of biocompatible, non-immunogenic, ultra-small size (<5.0 nm) quantum dots for nanomedicine loading that would be excreted through a renal clearance mechanism is highly awaited 21, 138, 139. Carbon nanotubes exert potential to cause toxicities in vivo and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, tremendous effort has been made to develop theranostic agents by bringing together the therapeutic and imaging components to synthesize a single molecule as well as by constructing nanoparticles and macromolecules loaded with those two components . The development of multimodal systems using various platforms such as fluorescent‐based drug delivery, drug–polymer conjugates, polymeric/magnetic/metal nanoparticles, dendrimers, liposomes, micelles, and carbon nanomaterials are some examples of those efforts. We and others have reported the modification of known therapeutics with common imaging agents such as DOTA .…”
Section: Introductionmentioning
confidence: 99%